Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1110/ps.034785.108
|View full text |Cite
|
Sign up to set email alerts
|

The structural basis of proteolytic activation of bovine glutamate dehydrogenase

Abstract: In this work, we re-examine the previously reported phenomenon of the creation of a superactive glutamate dehydrogenase by proteolytic modification by chymotrypsin and explore the various discrepancies that came to light during those studies. We find that superactivation is caused by cleavage at the N terminus of the protein and not the C-terminal allosteric site, as has previously been suggested. N-terminal sequencing reveals that TLCK-treated chymotrypsin cleaves bovine glutamate dehydrogenase at phenylalani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…This hypothesis is supported by the structural features of GDH as shown in Fig. 4b ; Asp6 and Asn8 form direct contacts with Lys329 through H-bonds and salt bridges, which therefore prevents the separation of fragments from the N-terminal region 36 . In addition, limited digestion experiments by Banerjee et al .…”
Section: Resultsmentioning
confidence: 72%
“…This hypothesis is supported by the structural features of GDH as shown in Fig. 4b ; Asp6 and Asn8 form direct contacts with Lys329 through H-bonds and salt bridges, which therefore prevents the separation of fragments from the N-terminal region 36 . In addition, limited digestion experiments by Banerjee et al .…”
Section: Resultsmentioning
confidence: 72%
“…In addition to the data presented above, previous MALDI studies demonstrated that the motility of this loop is diminished when the enzyme is locked into an abortive complex [30,31] and the α‐helix immediately upstream from this loop moves as the catalytic cleft opens and closes [30,31]. Recent studies have shown that chymotrypsin cleavage in this region removes this helical region, resulting in an activated form of the enzyme [41]. Finally, we recently determined the structures of two different drug–GDH complexes; these potent inhibitors were found to bind in the immediate vicinity of this zinc binding site.…”
Section: Resultsmentioning
confidence: 89%
“…19,20 As a consequence, any modication of these mechanisms through immobilization can alter the precise distribution of states within the native state ensemble 21,22 and modulate the allosteric response of the whole system. An example of a useful multimeric enzyme is the 336 kDa homohexameric protein glutamate dehydrogenase (GDH) from bovine liver, 23,24 which has its activity tightly controlled by a complex network of allosteric regulators 23,25 and its immobilization can induce differences in allosteric response. 26 In its immobilized form, glutamate dehydrogenase is normally used as glutamate probes, [27][28][29][30] employing different supports and methodologies for the attachment on a support.…”
Section: Introductionmentioning
confidence: 99%